Sosialisasi Pemanfaatan Hasil Pangan Lokal dengan Pengembangan Menu MP-ASI Sebagai Upaya Penurunan Angka Balita Stunting di Candimulyo, Magelang - Puji Lestari; Choirul Anwar; Muhammad Zia Ulhaq (Publikasi Indonesia, 2023)
Stunting is a growth and development failure experienced by children under five years of age as a result of a deficiency or chronic lack of nutrients and this event recurs especially during the golden period of the first 1000 days of life. Based on the 2018 Basic Health Research, it was informed that the prevalence of stunting in Indonesia was 30.8%, this percentage has decreased in the prevalence of stunting cases in 2017 with a decrease of 6.4%. Meanwhile, according to data from Basic Health Research (Riskesdas), the stunting rate in Magelang Regency in 2017 was at 37.6%. But it has slowly decreased in the last three years, namely by 20.23% in 2020. The purpose of this community service activity is to provide socialization about the use of local food as an appropriate source of MP-ASI as an effort to reduce the number of stunting toddlers. Increased knowledge of mothers about MP-ASI and how to give it properly is expected to contribute to preventing stunting. The method used in this community service activity is the joint discussion technique. The results obtained were the most local food sources produced from agriculture in Candimulyo District, namely corn and banana fiber sources. Based on the results of these discussions, it can be seen that around 95% of the participants, especially the cadres, already understand MP-ASI because they often practice making MP-ASI food and giving it to toddlers during Posyandu activities.